2020
DOI: 10.1002/apj.2497
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of pitch coke from oxidized polymerized pitch

Abstract: Refined polymerized pitch (RPP) is a by-product from the production of mesocarbon microbeads (MCMB). In order to understand the effects of an air oxidation treatment on the microstructure of the synthesized pitch coke, oxidized and polymerized pitch (prepared by oxidation in air with RPP as the raw material) has been used as the raw material to produce pitch coke. The microstructure of as-prepared pitch coke was determined using optical microscopy, scanning electron microscopy, XRD, and Raman spectroscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…The content of mosaic structures in the co-carbonization needle coke was much lower than that in CLP-C. Consequently, CLP-A 160% -C had the highest true density of 2.296 g cm −3 , which is in the range of high-quality needle coke according to the literature. 44,45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of mosaic structures in the co-carbonization needle coke was much lower than that in CLP-C. Consequently, CLP-A 160% -C had the highest true density of 2.296 g cm −3 , which is in the range of high-quality needle coke according to the literature. 44,45…”
Section: Resultsmentioning
confidence: 99%
“…The soening point (SP), coking value (CV), toluene insoluble (TI) and quinoline insoluble (QI) of the pitch were tested according to the literature. 28,29 The element content (C, H, N, and S) distribution was determined using an elemental analyzer (Vario ELIII, Elmentar, German) via the combustion method. Actually, the content of O was calculated using the difference method.…”
Section: Preparation Of Needle Coke By Co-carbonization Of Clp and An...mentioning
confidence: 99%
“…According to the literature, 30,32 the D band and G band were consisted with five isolated symmetrical peak. The five diffraction peaks were named as D1 peak (near 1350 cm −1 , caused by the disordered graphitic lattice [graphene layer edges, A 1g symmetry]), D2 peak (near 1620 cm −1 , caused by disordered graphitic lattice [surface graphene layers, E 2g ‐symmetry]), D3 peak (near 1500 cm −1 , caused by amorphous carbon), D4 peak (near 1200 cm −1 , caused by the disordered graphitic lattice, polyenes, ionic impurities), and G peak (near 1580 cm −1 , caused by the vibration of ideal graphitic lattice), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in the references, 25 carbon microcrystalline transformation characteristics of needle coke at low temperature can provide important information to predict the graphitization ability at high temperature. Some related reports suggested that the X‐ray diffraction and Raman spectrum combined with curve‐fitted method was the valuable way to obtain detailed information of carbon microcrystalline in carbonaceous materials 26–32 . In addition, the scanning electron microscope (SEM) and transmission electron microscope (TEM) were also the key methods to observe the microstructure of carbon materials 33–35 …”
Section: Introductionmentioning
confidence: 99%
“…The unique physicochemical properties of medium–low‐temperature coal tar pitch (MLP) make it an interesting material in many research fields 3 . It has been used as a feedstock for the production of added‐value materials such as liquid fuels, 4,5 mesophase pitch, 6 needle coke, 7 fine mosaic coke, 8 and activated carbon 9–13 …”
Section: Introductionmentioning
confidence: 99%